Small Garden - Brookes, John, 1933- (London Dorling Kindersley, 2006)
Ranging from initial inspiration to final layout, this book aims to help you create your own small garden. Whether you want a room outside for leisure and entertainment, or simply a space to call your own, it aims to help you achieve it in whatever space you have, from grassy lawn to balcony, roof terrace, window or passageway
Include Color Illustration and Idnex
Keywords: Gardens--Design -- Landscape gardening -- Gardening